Cardiovascular or renal disease (CVRD) complication and mortality incidence for type 2 diabetics with a single or without CVRD comorbidity: a 5-year SNDS nationwide claims database cohort study. (3rd October 2022) - Jourdain, P; Blin, P; Zaoui, P; Guiard, E; Sakr, D; Dureau-Pournin, C; Bernard, M A; Lassalle, R; Thomas-Delecourt, F; Bineau, S; Moore, N; Droz-Perroteau, C; et al.
Abstract: Background: Myocardial infarction (MI), stroke, peripheral arterial disease (PAD), heart failure (HF) and chronic kidney disease (CKD) are common cardiovascular renal disease (CVRD) complications for type 2 diabetes (T2D). However, for those with a single CVRD comorbidity, the incidence of a new CVRD complication and death is not well known. Purpose: To assess the 5-year CVRD complication and mortality incidence for T2D patients with a single CVRD comorbidity or without CVRD at baseline. Methods: A cohort study of all T2D patients with a single CVRD or without CVRD (disease-free) at baseline (January 1st, 2014) identified and followed-up for 5 years within the French SNDS nationwide claims database. Incidence rates were estimated for 5 years and the risk of all-cause death was compared to the disease-free population using Cox proportional hazards risk model: hazard ratio (HR) with [95% confidence interval]. Results: From about 2 million T2D patients without cancer or transplantation at baseline, 76.5% were disease-free, 7.9% with a single CVRD and the others having several CVRD comorbidities history. Five-year CVRD complication and mortality incidence rates for 1, 000 patient-years are presented in the table. CKD and HF were the most frequent CVRD complications for the disease-free and all CVRD comorbid populations, far ahead of MI, stroke and PAD, except PAD complication for PAD population and to a lesser degree stroke complication for stroke population. The incidence rate of all-cause death was the highest for HF+CKD patients, followed by HF patients, then PAD, stroke and CKD patients. Compared to disease-free patients with same sex and age, the HR of death was 4.3 [4.2–4.5] higher for HF+CKD patients, 2.7 [2.7–2.8], 2.1 [2.0–2.1], 2.1 [2.0–2.1], 1.9 [1.9–1.9] and 1.4 [1.3–1.4] for HF, CKD, PAD, stroke and MI patients, respectively. Conclusions: While MI, stroke and PAD comorbidities remain major risks of complications for T2D patients, HF and CKD nowadays represent a clearly higher risk of CVRD complications and death, that needs improved preventive strategies. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Study performed with unconditional funding from AstraZeneca